Analisis Harga Pokok Penjualan dan Biaya Produksi terhadap Laba Kotor - Adi Lesmana; Santi Widiawati (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2020)
In this study there are three variables, namely the variable X1 (Cost of Goods Sold), X2 (Production Costs) and the variable Y (Gross Profit). This research was conducted to determine The Effect of Cost of Goods Sold and Production Costs on Gross Profit (Case Study at PT. Gajah Tunggal Tbk in 2015- 2018). The method used in this research is an associative descriptive method with a quantitative approach. The data used are secondary data collected through library research, and documentation. While analyzing data using multiple linear regression analysis. Testing the hypothesis in this study using the T Test and F Test statistics with the help of the IBM Statistics SPSS 25.00 for Windows program. Based on the results of the study showed that the variable cost of goods sold and production costs have a positive and significant relationship to gross profit.